Characterization of phase‐transition‐induced micro‐domain structures in vanadium dioxide. (1st April 2014) - Lu, Ping; Zhou, Jiadong; Liu, Xinling; Zhang, Zongtao; Xu, Fangfang; Zhang, Linlin; Mou, Xinliang; Feng, Jingwei; Gao, Yanfeng; Zhao, Jingtai
<x xml:space="preserve">Abstract</x> The displacive structural phase transition of vanadium dioxide (VO2) from the high‐temperature tetragonal rutile (R) phase to the low‐temperature monoclinic M1 or M2 phase may induce the formation of a variety of domain structures. Here, all possible types of phase‐transition‐induced domain structures of the M1 and M2 phases have been theoretically formulated by using a general space group method. The predicted domain structures of the M1 phase, including mirror or rotation twins and antiphase domains, have been confirmed by transmission electron microscopy observation of VO2 powders and films, while the antiphase domains have never been involved in previous studies. The changes undergone by domain structures during a thermal or electron‐beam‐induced phase transition have been investigated. These results may suggest the potential influence of domain structures on the nucleation and progress of phase transitions, which unambiguously affect the hysteresis behavior of the first‐order transition of VO2.